The Functional Roles of IL-33/ST2 Axis in Ocular Diseases - Yujing Qian; Meifen Zhang (Hindawi Limited, 2020)
Interleukin-33 (IL-33), an important member of the IL-1 family, plays a pivotal role in regulating immune responses via combining with its receptor suppression of tumorigenicity 2 (ST2). We have already known IL-33/ST2 axis participates in the pathogenesis of various diseases, including liver diseases, renal diseases, and neurological diseases. Recently, emerging studies are indicating that IL-33/ST2 is also involved in a wide range of ocular diseases, such as allergic eye disease, keratitis and corneal regeneration, dry eye disease, uveitis, vitreoretinal diseases, and neuromyelitis optica spectrum disorder. In this review, we will summarize and discuss the current understanding about the functional roles of IL-33/ST2 in eyes, with an attempt to explore the possible study perspectives and therapeutic alternatives in the future.